Do silicon fertilizers improve the fodder value of tropical grass species? - Kindomihou, Valentin Missiakô; Ma, Jian Feng; SINSIN, Brice A.; Meerts, Pierre (My University, 2021)
Silicon has been reported as beneficial for promoting plant growth and yields. Tropical grasses species with higher concentration i.e. Pennisetum unisetum (＞13.5％ in blades), Panicum maximum Jacq (＞7.5%), and species having contents from 2.2 to 6.9% . How to reduce silica concentration in leaves for improving palatability, digestibility and nutrient value for animal high productivity? Effect of silicon supply on Silica accumulation and other structural and functional traits of some tropical fodder grass species was examined. Six tropical grasses were selected by their high forage value and because they provide essential tropical grassland biomass for animal consumption : Andropogon gayanus var Bisquamulatus (Hochst.) Hack, Brachiaria ruziziensis, Panicum maximum cultivar ORSTOM C1, Panicum maximum cultivar T673, Panicum maximum cultivar T58 and Panicum maximum Jacq. cultivar local. The soil used from Research Institute for Bioresources station of Kurashiki in Okayama University (Japan), is clayed. Complete randomized design in 3 replicates was prepared using silica gel treatments. Fractions that had passed a２mm sieve were used for pot culture. Grass clumps were cultured in pots for 2 weeks and transplanted in pots containing 3.3 kg of soil. Each pot contained 3 tillers per replicate in 3 replicates (i.e. 9 tillers per pot) and the soil was irrigated with distilled water daily. Soil received 0 or 100 g of silica gel for creating plus silicon and minus silicon treatments. Plants were grown in greenhouse for three months after transplantation (29 April‐29 July 2006), and harvested. Shoot biomass was measured. Si and P in shoots were analysed by the colorimetry using Spectrophotometer (Jasco, Japan). Leaf blades length, width, and leaf area, specific leaf area, specific leaf mass, leaf water content, shoot water content, leaf density and leaf thickness were recorded. ANOVA, Pearson Coefficient and Post hoc test were performed in STATISTICA 7.0. Shoot biomass increased significantly in response to Si supply and species respond differently in Si accumulation. P. maximum T58 showed the highest values for shoot biomass and P concentration while P . maximum C1 showed the lowest shoot biomass and the highest Si concentration. A. gayanus showed the lowest Si and P to Si supply . Globally, Si supply increased water content in shoots, as well as leaf dry matter and leaf area. Changes were also highlighted: negative correlation between shoot Si and blade width/blade dry matter, leaf Area and leaf density. Supplying silicon significantly increased both Si and P concentrations in shoot and blades which are the most grazed parts of fodder grasses. These results show that Silicon fertilizer could improved fodder value of some tropical grass species as previously suggested on fodder grasses, maize and other crops and rice.
Keywords: silicon fertilizer; grass silicification; fodder value; tropical; improve